2014
DOI: 10.1111/pbr.12211
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of critical factors affecting fitness of the sugary1 mutant in maize

Abstract: Fitness of sugary1 (su1) is affected by some critical traits that depend on the genotypes and environments, while their effects have not been quantified with convincing statistical methods. The objective of this work was to identify and quantify the critical factors of su1 fitness with different genotypes and environments. We used two pairs of field corn inbreds that differentially affected su1 viability to develop F 1 , F 2 , BC 1 and BC 2 . After selfing, Su1 and su1 kernels were evaluated under controlled e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Although, traits at early developmental stages, as early vigor, are the most important for su1 survival, other traits, as kernel yield, kernel moisture, plants height, ear length, and kernel row number, can also play a role in the survival of the mutant (Revilla et al 2000c). Djemel et al (2014) quantified the limiting factors affecting su1 viability and concluded that the importance of the effects affecting sugary1 fitness varied for each trait, depending on genotype, environment, and their interaction. The main critical factor for su1 fitness was early vigor, followed by emergence under cold conditions at the initial stages, while several adult traits were related with final fitness, particularly number of plants that produced grain.…”
Section: Introductionmentioning
confidence: 99%
“…Although, traits at early developmental stages, as early vigor, are the most important for su1 survival, other traits, as kernel yield, kernel moisture, plants height, ear length, and kernel row number, can also play a role in the survival of the mutant (Revilla et al 2000c). Djemel et al (2014) quantified the limiting factors affecting su1 viability and concluded that the importance of the effects affecting sugary1 fitness varied for each trait, depending on genotype, environment, and their interaction. The main critical factor for su1 fitness was early vigor, followed by emergence under cold conditions at the initial stages, while several adult traits were related with final fitness, particularly number of plants that produced grain.…”
Section: Introductionmentioning
confidence: 99%